Malignant transformation in mature cystic teratoma of ovary: Series of 4 cases - Gupta, Aruna; Katoch, Nandita; Shah, Garima; Gupta, Vikas; Verma, Nikhil (Journal of Pathology of Nepal, 2024)
Mature cystic teratoma is the most common benign ovarian tumour of germ cell origin. Malignant transformation is rare in mature cystic teratoma. Here we present a series of 4 cases showing malignant transformation in the form of squamous cell carcinoma, follicular carcinoma, and clear cell carcinoma in mature cystic teratoma. Our case series suggest that there should be suspicion of malignant transformation in mature cystic teratoma when they are present in perimenopausal and postmenopausal females.